In Vitro Cytotoxic Assessment of Functionalized Multi-walled Carbon Nanotubes Against Cervical Cancer - Chaturvedi V.K.; Tripathi A.D.; Minocha T.; Singh V.; Singh M.P.; Yadav D.P. (My University, 2025)
Cervical cancer is the most prevalent reproductive malignancy that affects the female reproductive system. A myriad of anti-cancer compounds has been used for its treatment, but the increasing mortality rates are still devastating. Currently, organic metal complexes are gaining popularity due to their anti-cancer attributes. Therefore, the current work was designed to assess the therapeutic efficacy of non-functionalized multi-walled carbon nanotubes (N-MWCNT) and functionalized MWCNTs (F-MWCNT) against cervical cancer. Initially, N-MWCNTs and F-MWCNTs were structurally characterized by various parameters, including FTIR, XRD, TEM, SEM, AFM, and EDAX. Our comparative study revealed that F-MWCNTs have a larger surface area and the presence of OH and COOH as functional groups, which are uniformly distributed in the tubular and crystalline structure. Furthermore, the MTT assay revealed IC50 values of 47.70 µg/ml and 61.94 µg/ml of N- MWCNTs and F-MWCNT, respectively; in that relation, our immunoblot results show upregulation of BAX and downregulation of BCL-2 in either of the cases, with N-MWCNT having 2.92 and 0.45 folds in comparison to 2.68 and 0.41 folds of F-MWCNT. Our results revealed that both materials inhibited cell proliferation and induced apoptosis in a dose-dependent manner. Still, the effect of N-MWCNTs was more prominent as compared to F-MWCNTs. The overall conclusions of this study indicated that doses of F-MWCNTs could be explored for the safe drug delivery vehicle used as an effective biocompatible nanoformulation agent and this will open a new door for cervical cancer treatment. © 2023, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.